Using taylor series expansion obtain a power series solution to the initial value problem
(2x2-3)d2y/dx2-2xdy/dx+y=0 y(0)=1 y'(0)=7
Solution;
The Taylor's series expansion of f(x) about x=a is;
"f(x)=f(a)+f'(a)(x-a)+\\frac{f''(a)}{2!}(x-a)^2+\\frac{f'''(a)}{3!}(x-a)^3+..."
The series solution about x=0 can be written as;
"y(x)=y(0)+y'(0)x+\\frac{y''(0)}{2!}x^2+\\frac{y'''}{3!}x^3+..."
Given y(0)=1 and y'(0)=0;
Also;
"(2x^2-3)\\frac{d^2y}{dx^2}-2x\\frac{dy}{dx}+y=0"
At x=0,
"(0-3)\\frac{d^2y}{dx^2}-(0)(7)+1=0"
"-3\\frac{d^2y}{dx^2}=-1"
"y''=\\frac13"
By distribution,we write the equation as,
"2x^2\\frac{d^2y}{dx^2}-3\\frac{d^2y}{dx^2}-2x\\frac{dy}{dx}+y=0"
Differentiate by applying product rule;
"[2x^2\\frac{d^3y}{dx^3}+\\frac{d^2y}{dx^2}(4x)]-3\\frac{d^3y}{dx^3}-[2x\\frac{d^2y}{dx^2}+2\\frac{dy}{dx}]+\\frac{dy}{dx}=0"
At x=0;
"(0+0)-3\\frac{d^3y}{dx^3}-(0+(2\u00d77))+7=0"
"-3\\frac{d^3y}{dx^3}=-21"
y'''=7
Hence ,the power series solution give by ;
"y(x)=y(0)+y'(0)x+\\frac{y"(0)}{2!}x^2+\\frac{y'''(0)}{3!}x^3+..."
By substitution ,will be;
"y(x)=1+7x+\\frac16x^2+\\frac76x^3+..."
Comments
Leave a comment